2011
DOI: 10.5530/ax.2011.2.4
|View full text |Cite
|
Sign up to set email alerts
|

Influence on the Carotenoid Levels of Skin Arising from Age, Gender, Body Mass Index in Smoking/Non-Smoking Individuals

Abstract: Introduction: Intakes of fruit and vegetables rich in carotenoids are associated with a lower risk for a variety of chronic diseases. Therefore, the carotenoid levels in the skin have been measured in various studies to investigate the effects of nutrition and lifestyle. However, statistically clear data regarding the influence of age, gender, body mass index, and smoking behaviour were not documented. Methods: Thus, non-invasive resonance Raman measurements were performed on 151 healthy volunteers in Berlin, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
19
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 32 publications
7
19
1
Order By: Relevance
“…Above all, as in previous studies, we found stress conditions to influence the individual antioxidant status notably [17,39]. The individual variety of stress exposition and stress management can explain the broad variance found in all three ethnic groups despite the relatively uniform dietary habits regarding high vegetable intake in South Korea.…”
Section: Resultssupporting
confidence: 51%
See 2 more Smart Citations
“…Above all, as in previous studies, we found stress conditions to influence the individual antioxidant status notably [17,39]. The individual variety of stress exposition and stress management can explain the broad variance found in all three ethnic groups despite the relatively uniform dietary habits regarding high vegetable intake in South Korea.…”
Section: Resultssupporting
confidence: 51%
“…Therefore, conducting a gender-adjusted multi-factor ANCOVA, the effects of population group, age group and stress on antioxidant concentrations were determined. Previous studies showed that the antioxidant status is independent of age [39]. However, evaluating the questionnaires of all volunteers in our study, we found a significant effect of age group on the carotenoid concentration at the p < 0.05 level for the three conditions (F = 7.376, p = 0.007).…”
Section: Resultscontrasting
confidence: 42%
See 1 more Smart Citation
“…More specifically, Meinke et al observed that obese subjects (BMI ≥ 30) had 13% lower skin carotenoids, as measured by RRS, compared to normal/overweight subjects (BMI < 30), p < 0.05. 56 Rerksuppaphol and Rerksuppaphol also observed lower skin carotenoid status in obese subjects relative to normal weight subjects, but the association with obesity was not significant. 52 In our own work in adults, the highest skin carotenoid values were observed in subjects who were underweight or normal body weight, although there was no trend and the association was not significant.…”
Section: 0 Biomarker Development: Intra- Versus Inter-subject Variamentioning
confidence: 76%
“…40,42 This has subsequently been observed in other studies. 43,56 More specifically, smokers had about a 20–30% reduction in skin carotenoid levels when compared to non-smokers. Because some of this effect is likely due to lower intake of carotenoids (in addition to the direct effects of tobacco-induced oxidation of carotenoids), we performed multivariate analyses in one of our studies, which showed, after correcting for dietary intake, that smoking was still associated with lower carotenoid status at baseline, although the p value was marginally significant (p = 0.07).…”
Section: 0 Biomarker Development: Intra- Versus Inter-subject Variamentioning
confidence: 99%